2001
DOI: 10.1016/s0735-1097(01)01402-4
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic drug therapy in the Multicenter UnSustained Tachycardia Trial (MUSTT): drug testing and as-treated analysis

Abstract: Even when presenting the results as favorably as possible, we found no benefit with PVS-guided drug therapy in patients with clinical unsustained VT who had inducible sustained VT. These findings are unaltered by using different end points for PVS or considering the response to individual drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…Patients presenting with syncope or sustained palpitations who have evidence of myocardial scar as well as those with a widecomplex tachycardia for whom the diagnosis of VT is not certain may benefit from a provocative EPS. Although the standalone negative and positive predictive values of this testing are limited, [88,120] inducible SMVT is highly associated with recurrent VT and may provide clues to the cause of syncope or other symptoms suggestive of a VA. Electroanatomical mapping of the RV has been used to identify otherwise unapparent RV scar [121,122].…”
Section: Invasive Electrophysiological Studymentioning
confidence: 99%
“…Patients presenting with syncope or sustained palpitations who have evidence of myocardial scar as well as those with a widecomplex tachycardia for whom the diagnosis of VT is not certain may benefit from a provocative EPS. Although the standalone negative and positive predictive values of this testing are limited, [88,120] inducible SMVT is highly associated with recurrent VT and may provide clues to the cause of syncope or other symptoms suggestive of a VA. Electroanatomical mapping of the RV has been used to identify otherwise unapparent RV scar [121,122].…”
Section: Invasive Electrophysiological Studymentioning
confidence: 99%
“…Disagreement among these studies can be explained by differences in stimulation protocols, loading and maintenance doses of amiodarone, and duration of follow‐up. Also, the Multicenter Unsustained Tachycardia Trial showed no benefit of EP testing among patients assigned to antiarrhythmic drugs, 12 although most of them used Vaughn Williams Class I drugs, and a nonsignificant better survival in patients on sotalol also was observed 11 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…Однако в исследовании MUSTT [30] при оценке эффективности БАБ, антиаритмиков и ИКД у пациентов с ИБС, ФВ ЛЖ менее 40% и нестойкой ЖТ было выявлено, что группа пациентов, находившихся на БАБ, ассоциировалась со снижением общей смертности (50% против 66% у пациентов без БАБ, р=0,0001), однако значимого снижения ВСС достигнуто не было (p=0,2344). Снижение риска аритмических событий также было недостоверно и составило от 12 до 19%.…”
Section: бета-блокаторы в профилактике вссunclassified